Sound quality design of consumer electronics based on requirement analysis considering use case (Design information management using multidomain matrix) - Kazuko YAMAGISHI; Koichi OHTOMI; Kenichi SEKI; Hidekazu NISHIMURA (Nihon Kikai Gakkai ronbunshu, 2018)
The sound quality design of consumer electronics spans multiple design processes, from requirement definition to functional and structural design. It is difficult to reflect customer demands depending on situations to physical design. In this paper, we introduce the evaluation grid method that assumes use cases to clarify customer demands for camera shutter sound depending on situations. To define the sound quality target, customer demands according to use cases are derived from clustering analysis of the evaluation grid test for camera shutter sound. Using domain mapping matrix, we define the relationships between use cases and requirement clusters, requirement clusters and evaluation words for sensory test, evaluation words and tonal factors. By this method, it is possible to evaluate the customer requirements depending on use cases, and define the sound quality target. In order to solve a problem in which relationship among customer requirements, functional and structural design are not clear, we propose an MDM-based representation to show the design information management from requirement definition to functional and structural design. In the requirement definition process, sound quality targets depending on use cases are defined using tonal factors. In order to systematically connect to sound quality metrics in the functional design process and to engineering metrics in the structural design process, DSM and DMM were used. The method was applied to camera shutter sound design and shows its effectiveness.